2021
DOI: 10.7759/cureus.15668
|View full text |Cite
|
Sign up to set email alerts
|

Primary Clear Cell Carcinoma of the Pancreas: A Systematic Review

Abstract: Over the years, the world has witnessed many advances in diagnosing and treating multiple types of cancers. These breakthroughs have revolutionized the understanding of the molecular drive behind these neoplasms, leading to tangible therapeutic evolution and promising prognostic implications. However, pancreatic cancer remains a highly lethal disease. With recent discoveries, modern medicine has been able to delineate histopathologic subtypes of pancreatic cancer in hopes of improved diagnosis and treatment to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Although data on incidence and follow-up are currently limited, previous reports have described CCCP as an aggressive histological variant of PDAC, associated with poor patient outcomes [11]. In this report, we applied ultrastructural TEM analysis to a CCCP surgical specimen from a 65-year-old patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although data on incidence and follow-up are currently limited, previous reports have described CCCP as an aggressive histological variant of PDAC, associated with poor patient outcomes [11]. In this report, we applied ultrastructural TEM analysis to a CCCP surgical specimen from a 65-year-old patient.…”
Section: Discussionmentioning
confidence: 99%
“…Clear-cell carcinoma of the pancreas (CCCP) is a rare morphological pattern of ductal adenocarcinoma that is not yet fully defined. It was first observed by Cubilla et al in 1980 [10], and only a few cases have been reported since [11]. CCCP presents with tumor cells that have clear cytoplasm and hyperchromatic nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…Clear cell carcinoma of the pancreas is not a well-known entity and can be diagnostically misleading [83,84]. Kim et al, in the study of 84 pancreatic cancer specimens, reported that 24% of the analyzed cases contained significant clear cell components, and 14% of the studied cohort was defined as having clear cell carcinoma with over 75% of the tumor volume showing clear cell features [85].…”
Section: Morphological Heterogeneitymentioning
confidence: 99%
“…In differentiating clear-cell-appearing tumors in the pancreas, other entities have to be taken into consideration, such as metastatic clear cell renal cell carcinomas, ovarian and adrenal carcinomas, and primary clear cell neuroendocrine tumors of the pancreas (frequently occurring in patients with von Hippel-Lindau disease) [86,87]. In the differential diagnosis, various histopathological stainings come in handy, including immunohistochemistry for carbonic anhydrase IX, HMB45, vimentin, PAX8, CD10, synaptophysin, or chromogranin [83]. Particularly useful for diagnosing clear cell pancreatic carcinoma of ductal origin (exocrine) is hepatocyte nuclear factor-1β (HNF1B), which significantly shows a stronger positivity more frequently in clear cell components compared to conventional ductal adenocarcinomas [85].…”
Section: Morphological Heterogeneitymentioning
confidence: 99%